Cellular Inflammatory Markers and Castelli Risk Indices in Women with Gestational Diabetes Mellitus - Rahamon, Sheu Kadiri; Oladeji, David Olaniyi; Yaqub, Surajudeen Adebayo; Akinlade, Kehinde Sola (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: The clinical importance of early identification of potential predictors of cardiovascular events in women with gestational diabetes mellitus (GDM) cannot be overemphasized. This study aimed to determine the plasma levels of Castelli risk indices (CRI) and selected cellular inflammatory markers in women with GDM.Methods: A total of 40 pregnant women, consisting of 11 women with GDM and 29 women without GDM, were randomly enrolled into this case-control study using the convenient sampling method. Venous blood samples were taken. The plasma lipid profiles were determined using the spectrophotometric methods. White blood cell differential was counted using a microscope. Plasma levels of CRI-I, CRI-II, low-density lipoprotein cholesterol (LDL-C), neutrophil-lymphocyte ratio (NLR), and monocyte lymphocyte ratio (MLR) were calculated using the appropriate formula. Student’s t-test, Mann Whitney U, Chi-square, and Spearman’s rho correlations were used for statistical analysis. P<0.05 was considered statistically significant. Results: The CRI-I [6.58(6.06–7.60) vs 3.42(2.83–3.89)], CRI-II [4.59(4.17–5.28 vs 1.82(1.36–2.16)) and NLR (3.72±0.52 vs 2.63±0.61) were significantly higher in women with GDM. Likewise, the mean age (34.18±3.49), gestational weight (92.82±11.23), fasting plasma glucose (FPG) (98.45±6.24), total cholesterol (TC) (310.92(290.81–360.78)), triglyceride (TG) (232.86(221.28–256.00), LDL-C (214.85(206.24–239.80), and neutrophil count (76.36±2.58) were significantly higher in women with GDM (p<0.05). In contrast, HDL-C (45.56(44.90–51.34), lymphocytes (20.82±2.14), and monocytes counts (2.73±1.10) were significantly lower in women with GDM. However, there was no difference in the MLR between the two groups.Conclusion: The CRI-I, CRI-II, and NLR are significantly elevated in women with GDM. Dyslipidemia and systemic inflammation are associated with GDM, which are forerunners of cardiovascular diseases.